Application of PDCA cycle management to improve the nursing quality and work enthusiasm of nursing staff in the Geriatric Department (运用PDCA循环管理法提升老年病科护理人员护理质量和工作积极性) - LIU Yang (刘洋) (中西医结合护理)
Objective To investigate the effect of Plan-Do-Check-Action(PDCA) cycle management on improving the nursing quality and work enthusiasm of nursing staff in the Geriatric Department. Methods Totally 29 nurses form two clinical wards of the Geriatric Department were recruited and divided into the observation group (n=15) and control group (n=14). The conventional method of nursing quality management was adopted in the controlgroup, while the PDCA cycle management tools were used to improve the nursing quality in the observation group. The quality of nursing, work enthusiasm, work status, and satisfaction of nursing staff with management were measured and compared between two groups. Results The score of nursing quality assessment in the observation group was significantly higher than that of the control group(P<0. 01). Nurses in the observation group had reported a higher level of e work enthusiasm compared with those in the control group(P<0. 01). The Gallup Q12 Workplace Audit (GWA) score and the Connor Davidson Resilience Scale (CD-RISC) score in the observation group were higher than those in the control group(P<0. 01); The Maslach Burnout Inventory(MBI)score of the observation group was significantly lower than that of the control group (P<0. 01). The satisfaction score of nursing staff in the observation group was significantly higher than that in the control group(P<0. 01). Conclusion The application of PDCA cycle management can effectively improve quality of geriatric nursing and work efficiency of nursing staff, which is worthy of clinical promotion. (目的 探讨PDCA循环管理法提升老年病科护理人员护理质量及工作积极性的效果。方法 选取老年病房两个科室共计29名护理人员为研究对象, 分为观察组(n=15)和对照组(n=15)。对照组接受常规护理管理方法, 观察组将PDCA循环管理法融入常规护理管理。对比分析两组护理人员护理质量、工作积极性、工作状态, 评价护理人员对护理管理工作的满意度。结果 观察组护理人员的护理质量评分高于对照组, 差异有统计学意义(P＜0. 01)。观察组护理人员的工作积极性评价优于对照组(P＜0. 01), 盖洛普Q12调查表(GWA)评分和Connor-Davidson心理弹性量表(CD-RISC)评分均高于对照组(P＜0. 01), 职业倦怠量表(MBI)评分低于对照组(P＜0. 01), 满意度量表评分高于对照组(P＜0. 01)。结论 应用PDCA循环管理法能够有效提高老年病科护理质量, 提升护理人员的工作效率。)